2014
DOI: 10.1111/aas.12335
|View full text |Cite
|
Sign up to set email alerts
|

The influence of glucose load on metabolism during minor surgery using remifentanil-induced anesthesia

Abstract: Infusion of low-dose glucose attenuated fat catabolism without causing hyperglycemia, indicating that infusion of low-dose glucose during remifentanil-induced anesthesia may be safe for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 25 publications
2
18
2
Order By: Relevance
“…However, no significant differences were observed among the three groups. In previous studies, the plasma levels of ketone bodies and FFA were used to assess fat catabolism [1][2][3][4][5][6][7]. Similarly, we evaluated ketone bodies and FFA in the present study as well.…”
Section: Figurementioning
confidence: 98%
See 4 more Smart Citations
“…However, no significant differences were observed among the three groups. In previous studies, the plasma levels of ketone bodies and FFA were used to assess fat catabolism [1][2][3][4][5][6][7]. Similarly, we evaluated ketone bodies and FFA in the present study as well.…”
Section: Figurementioning
confidence: 98%
“…Previous studies have demonstrated the inhibition of catabolism by the administration of glucose under general doi: 10.7243/2049-9752-6-1 anaesthesia at a rate of 0.07-0.25 g/kg/ h [1][2][3][4][5][6][7], whereas hyperglycaemia was detected in studies in which more than 0.15 g/kg/h of glucose were administered. We demonstrated that the mean energy expenditure (EE) value of operative patients was 17.7kcal/kg/day in a previous study [17].…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations